Making polyurethanes from castor oil with addition of bentonite and chitosan as coating paints on eco-friendly medical device applications - Rihayat, T.; Suryani, Suryani; Riskina, S.; Siregar, J. P.; Jaafar, J.; Cionita, T.; Fitria, Fitria (2020)
Polyurethane-based vegetable oil coatings have been used in the past few decades considering the use of petrochemical-based raw materials is a non-renewable material. Vegetable oils used such as soybean oil, palm oil, and castor oil. They have lower environmental impacts, easy availability and biodegradation. In this study, polyurethane synthesis was carried out using the prepolymer method using the reaction of TDI with polyols based on castor oil. To provide anti-microbial properties of polyurethane, a composite method of polyurethane with chitosan was carried out. Whereas to provide heat resistance properties in polyurethane bentonite is added to polyurethane. Polyurethane/bentonite/nanocomposite chitosan was analyzed using the Fourier Transform Infrared Spectra (FTIR) to determine the microstructure of chemical compounds, Thermal Gravimetric Analysis (TGA) for viewing polyurethane/bentonite/chitosan heat resistance, and Scanning Electron Microscope (SEM) to see the morphology of polyurethane/ bentonite/chitosan. FTIR analysis have shown the formation of hydroxyl groups in the compound epoxide castor oil, the reaction lasts for 2.5 hours at 50 o C as evidenced by the absorption of OH wave numbers which widens at 3500 cm-1, the hydroxy group formed is the hydroxy group on C atoms secondary, and bentonite NH 3450 cm-1, chitosan cluster C = O urethane widened at 1772 cm-1. TGA analysis have pure polyurethane begins to decrease in mass at 246 o C, while polyurethane with the addition of filler decreases mass at 342 o C.